(untitled) (El Hilo de la Fabula, 2020)
An argumentative–notional poem by Janet Frame is the basis for the analysis of domestication vs foreignization to define translation as a creative act. Benjamin’s image of the circle is used to reflect on the performative nature of translation as well as a platform for understanding the interstices in cultural translation. Contrastive method (source text–version) is applied from a translation theory perspective. An interpretative-didactic illustration achieved in the literature classroom is added to the analysis.